Maintenance Management Systems in the Czech Enterprises of Chemical and Food Industries - Branská, Lenka; Pecinová, Zuzana; Paták, Michal; Staňková, Monika; Kholová, Pavla (My University, 2016)
Maintenance of production equipment in industrial enterprises plays an increasingly important role. It is quite obvious that it can eliminate a number of risks associated with the business and ensure effective use of financial resources necessary to ensure the working order of the machinery and equipment of the businesses. Production equipment maintenance systems are irreplaceable in chemical and food industry enterprises, but there is great potential for improvement. The article solves the main opportunities for the maintenance systems improvement by the results of the qualitative research in five companies, which can be regarded as typical representatives of the industries. The results of the research allowed to identify the main opportunities for the maintenance systems improvement. Improvement should be focused on the area of strategic as well as tactical and operational planning of production equipment maintenance. In terms of strategy, the biggest opportunity for a dramatic improvement is the implementation of modern maintenance methods. In the context of the existing systems, improvement can be achieved especially in setting strategic objectives, the system of indicators to measure the performance of maintenance and in implementing an information system. In the tactical and operational level, it would be useful to develop a maintenance planning system linked with suppliers and customers and utilize mathematical methods and models to optimize plans for this business activity.
Systémy managementu údržby v českých podnicích chemického a potravinářského průmyslu
Keywords: maintenance; maintenance systems; production equipment; chemical industry; food industry; údržba; systémy údržby; výrobní zařízení; chemický průmysl; potravinářský průmysl